Molecular fingerprint of female bovine embryos produced in vitro with high competence to establish and maintain pregnancy. Issue 2 (16th October 2019) - Zolini, A M; Block, J; Rabaglino, M B; Tríbulo, P; Hoelker, M; Rincon, G; Bromfield, J J; Hansen, P J
Abstract: The objective was to identify the transcriptomic profile of in vitro-derived embryos with high competence to establish and maintain gestation. Embryos produced with X-sorted sperm were cultured from day 5 to day 7 in serum-free medium containing 10 ng/ml recombinant bovine colony-stimulating factor 2 (CSF2) or vehicle. The CSF2 was administered because this molecule can increase blastocyst competence for survival after embryo transfer. Blastocysts were harvested on day 7 of culture and manually bisected. One demi-embryo from a single blastocyst was transferred into a synchronized recipient and the other half was used for RNA-seq analysis. Using P  < 0.01 and a fold change >2-fold or <0.5 fold as cutoffs, there were 617 differentially expressed genes (DEG) between embryos that survived to day 30 of gestation vs those that did not, 470 DEG between embryos that survived to day 60 and those that did not, 432 DEG between embryos that maintained pregnancy from day 30 to day 60 vs those where pregnancy failed after day 30, and 635 DEG regulated by CSF2. Pathways and ontologies in which DEG were overrepresented included many related to cellular responses to stress and cell survival. It was concluded that gene expression in the blastocyst is different between embryos that are competent to establish and maintain pregnancy vs those that are not. The relationship between expression of genes related to cell stress and subsequent embryonic survival probably reflects cellular perturbations caused by embryonic development taking place in the artificial environment associated with cell culture. Abstract : Summary sentence : Embryos produced in vitro that are capable of maintaining gestation have a gene expression pattern that diverges from embryos that fail to establish pregnancy.